Transcriptome profiling uncovers β-galactosidases of diverse domain classes influencing hypocotyl development in jute (Corchorus capsularis L.). (December 2018) - Satya, Pratik; Chakraborty, Avrajit; Sarkar, Debabrata; Karan, Maya; Das, Debajeet; Mandal, Nur Alam; Saha, Dipnarayan; Datta, Subhojit; Ray, Soham; Kar, Chandan Sourav; Karmakar, Pran Gobinda; Mitra, Jiban; et al.
Abstract: Enzyme β-galactosidase (EC 3.2.1.23) is known to influence vascular differentiation during early vegetative growth of plants, but its role in hypocotyl development is not yet fully understood. We generated the hypocotyl transcriptome data of a hypocotyl-defect jute ( Corchorus capsularis L.) mutant (52, 393 unigenes) and its wild-type (WT) cv. JRC-212 (44, 720 unigenes) by paired-end RNA-seq and identified 11 isoforms of β-galactosidase, using a combination of sequence annotation, domain identification and structural-homology modeling. Phylogenetic analysis classified the jute β-galactosidases into six subfamilies of glycoside hydrolase-35 family, which are closely related to homologs from Malvaceous species. We also report here the expression of a β-galactosidase of glycoside hydrolase-2 family that was earlier considered to be absent in higher plants. Comparative analysis of domain structure allowed us to propose a domain-centric evolution of the five classes of plant β-galactosidases . Further, we observed 1.8–12.2-fold higher expression of nine β-galactosidase isoforms in the mutant hypocotyl, which was characterized by slower growth, undulated shape and deformed cell wall. In vitro and in vivo β-galactosidase activities were also higher in the mutant hypocotyl. Phenotypic analysis supported a significant ( P  ≤ 0.01) positive correlation between enzyme activity and undulated hypocotyl. Taken together, our study identifies the complete set of β-galactosidases expressed in the jute hypocotyl, and provides compelling evidence that they may be involved in cell wall degradation during hypocotyl development. Graphical abstract: Image 1 Highlights: We generated hypocotyl transcriptomes from mutant and wild-type jute annotating 39, 076 genes. We characterized the complete array of β-galactosidases expressed in jute hypocotyl. A domain-centric classification of plant β-galactosidases helps to explain their evolution. We elucidated the evolution of a prokaryotic β-galactosidase previously undescribed in plant. Our study indicates a crucial role of β-galactosidase in hypocotyl development.